1992
DOI: 10.1093/infdis/166.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Herpesvirus 6 in Tissues Involved by Sinus Histiocytosis with Massive Lymphadenopathy (Rosai-Dorfman Disease)

Abstract: After preliminary serologic data demonstrated elevated antibody titers to human herpesvirus (HHV) 6 in patients with sinus histiocytosis with massive lymphadenopathy (SHML) or Rosai-Dorfman disease, tissues were examined from 9 patients with classical SHML to search for evidence of HHV-6 infection. Involved tissues from 7 of the 9 patients had detectable HHV-6 by in situ hybridization: Tissue from 1 had detectable Epstein-Barr virus genome but no HHV-6 and tissue from another had no detectable HHV-6 or Epstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
2
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(131 citation statements)
references
References 27 publications
5
121
2
3
Order By: Relevance
“…Clearly, the most interesting finding is represented by the demonstration of a HHV-6 protein in the late phase of the viral cycle in a significant proportion of the abnormal histiocytes, which represent the hallmark of the Rosai-Dorfman disease. Our study extends the results by Levine and colleagues, 44 who documented the presence of HHV-6 DNA in such cells by in situ DNA hybridization. The novelty and the interest of our finding is that we provide the first evidence that HHV-6 not only may infect the abnormal histiocytes of Rosai-Dorfman disease but, more importantly, it is functionally active in such cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clearly, the most interesting finding is represented by the demonstration of a HHV-6 protein in the late phase of the viral cycle in a significant proportion of the abnormal histiocytes, which represent the hallmark of the Rosai-Dorfman disease. Our study extends the results by Levine and colleagues, 44 who documented the presence of HHV-6 DNA in such cells by in situ DNA hybridization. The novelty and the interest of our finding is that we provide the first evidence that HHV-6 not only may infect the abnormal histiocytes of Rosai-Dorfman disease but, more importantly, it is functionally active in such cells.…”
Section: Discussionsupporting
confidence: 91%
“…Rosai-Dorfman disease has been proposed to represent an exaggerated immunological response to an infectious agent, and a pathogenetic association with EBV has been previously reported. 44,45 Thus, we suggest that HHV-6 should also be investigated as another possible trigger of the uncontrolled proliferation of abnormal histiocytes in such disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that human herpesvirus (HHV)-6 may play a role in the pathogenesis of SHML. HHV-6 is a ubiquitous virus that infects most individuals in childhood and remains latent in host cells; infection can be reactivated by immunodeficiency (17,18). HHV-6 causes exanthem subitum (sixth disease) in children and hepatitis, encephalitis, and opportunistic infections in patients who have acquired immunodeficiency syndrome and in transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Various stimuli could trigger this functional activation, like coexistence of RDD and autoim-mune diseases, haematological malignancies and post-infectious conditions. In fact, many viruses like Herpesvirus 6 (HHV-6) (6) and Epstein-Barr virus (EBV) (7) have been implicated as potential causative agents, however, there is no strong evidence for this at the moment. Pathology Histologically, in the lymph nodes one can see heavily infiltrated large histiocytes, lymphocytes and plasma cells showing pericapsular fibrosis and dilated sinuses.…”
Section: Discussionmentioning
confidence: 99%